2013
DOI: 10.1080/10926771.2013.743939
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Readiness to Change in Victims of Intimate Partner Violence

Abstract: Intimate partner violence (IPV) is a social problem associated with significant morbidity; however, victims don’t always utilize treatment and resources. One’s readiness to change may be one variable impacting their pursuit of treatment and other resources. The current study investigated correlates of readiness to change, and readiness to change’s impact on treatment utilization. Data was collected from 223 women residing in battered women’s shelters. Correlational analyses find that generally victims with mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In addition, African American women compared with women of other races have been found to be at later SOC (Alexander et al, 2009). In addition to demographics, higher levels of psychopathology, distress, self-esteem, spiritual well-being, and social support have been found to contribute to a woman's readiness to change (Bliss, Ogley-Oliver, Jackson, Harp, & Kaslow, 2008;N. L. Johnson & Johnson, 2013;Shurman & Rodriguez, 2006).…”
Section: The Process Of Change In Survivors Of Ipvmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, African American women compared with women of other races have been found to be at later SOC (Alexander et al, 2009). In addition to demographics, higher levels of psychopathology, distress, self-esteem, spiritual well-being, and social support have been found to contribute to a woman's readiness to change (Bliss, Ogley-Oliver, Jackson, Harp, & Kaslow, 2008;N. L. Johnson & Johnson, 2013;Shurman & Rodriguez, 2006).…”
Section: The Process Of Change In Survivors Of Ipvmentioning
confidence: 99%
“…The manner in which researchers have measured social support may be one contributing factor to the mixed results. For example, structural support, defined as the size of an individual's support network (Procidano & Heller, 1983), has been found to be both unrelated (Alexander et al, 2009) and positively associated with readiness to change (N. L. Johnson & Johnson, 2013). Qualitative and quantitative research have demonstrated that functional support, defined as emotional and practical aid received by a social support network, is an important contributor to seeking safety and obtaining a violence free life and maintaining such a change (Levendosky et al, 2004;Short et al, 2000).…”
Section: Social Support and The Process Of Changementioning
confidence: 99%
“…Thus, social support can act as a potential resiliency factor that can offset the negative consequences of having experienced ACEs. Not only can social support mitigate the risk of conflict within intimate relationships, but greater social support has also been associated with leaving an abusive relationship (Johnson & Johnson, 2013). While previous research has found that interventions that promote social support and community advocacy improved mental health outcomes among survivors of IPV (e.g., Constantino et al, 2005;Ogbe et al, 2020), enhancing social support, for example including community members as a resource (e.g., Ogbe et al, 2020), may be a beneficial prevention strategy for IPV, particularly among individuals with elevated ACEs scores.…”
Section: Future Directionsmentioning
confidence: 99%
“…Greater problem severity may enhance readiness to change because the status quo is uncomfortable and impairing. Greater mental health symptom severity is associated with later SOC in intimate partner violence victims (Edwards et al, 2006; Johnson & Johnson, 2013). More severe alcohol problems are associated with higher readiness to reduce alcohol use (Alley et al, 2018; Williams et al, 2006).…”
Section: Predictors Of Stage Of Changementioning
confidence: 99%